Occurrence of Virulence Genes and Antimicrobial Resistance of E. coli O157:H7 Isolated from the Beef Carcass of Bahir Dar City, Ethiopia - Habtamu Yalew Ayenew; Birhan Agmas Mitiku; Tesfaye Sisay Tesema (Veterinary Medicine International)
E. coli O157:H7 is one of the most virulent foodborne pathogens. The aim of this study was to isolate E. coli O157:H7, determine virulence genes carried by the organism, and assess the antimicrobial susceptibility pattern of the isolates from beef carcass samples at Bahir Dar city. Swab samples (n = 280) were collected from the carcass of cattle slaughtered at the abattoir and processed using sorbitol MacConkey agar supplemented with cefixime telluride and confirmed with latex agglutination test. A polymerase chain reaction was performed on isolates for the detection of virulence genes stx1, stx2, hlyA, and eae. Antimicrobial susceptibility testing was performed using the disk diffusion method. Of 280 samples processed, 25 (8.9%) isolates were positive. Out of 25 isolates subjected for molecular detection, 8 (32%) and 14 (56%) isolates possessed stx1 and stx2 genes, respectively; from those, 5 (20%) isolates had both genes for the production of Shiga toxins. Compared from other virulent genes relatively higher proportion of 18 (72%) isolates carried the hlyA gene. Only 5 (2%) isolates were positive for eae. Resistance was detected in all 25 (100%) isolates and 3 (12%) against clindamycin and trimethoprim, respectively. This study result highlights the potential threat to public health. The abattoir workers need to be aware about the pathogen and should follow appropriate practices to prevent contamination of meat intended for human consumption.